Di-functional luminescent sensors based on Y3+ doped Eu3+ and Tb3+ coordination polymers: fast response and visible detection of Cr3+, Fe3+ ions in aqueous solutions and acetone. Issue 53 (1st September 2020) - Liu, Hongyan; Liu, Yang; Meng, Yu; Shi, Xiaolei; Sun, Junshan; Zhao, Limin; Chen, Diming; Hao, Hongguo; Li, Dacheng; Dou, Jianmin; Han, Jun
Abstract : Two series of doped coordination polymers (Eu x Y1− x and Tb x Y1− x ) through isomorphous substitution method utilizing Y 3+ in place of partial Eu 3+ /Tb 3+ were obtained. The doped materials could detect Fe 3+, Cr 3+, and acetone selectively and sensitively. Abstract : With the careful modulation of the relative ratio of Y 3+ /Eu 3+ and Y 3+ /Tb 3+, two series of bimetallic RE-CPs (Eu x Y1− x and Tb x Y1− x ) were successfully obtained through the isomorphous substitution method. Interestingly, the introduction of Y 3+ ions does not change the fluorescence characteristic peak of 1-Eu and 1-Tb, but enhances its fluorescence lifetime and quantum yield. Experimental and theoretical simulation results show the co-doping process changes the intramolecular energy transfer process and reduces the non-radiative transition resulting from concentration quenching. Eu0.1 Y0.9 and Tb0.1 Y0.9 with the largest luminescence lifetime were selected as the representative research objects, their potential application for the detection of toxic metal ions and organic molecules was further investigated. Interestingly, Eu0.1 Y0.9 and Tb0.1 Y0.9 demonstrate high sensitivity and good selectivity towards Fe 3+, Cr 3+ and acetone. Besides, fine fluorescence visibility provides the necessary conditions for the preparation of simple and fast response fluorescent test papers in order to achieve real-time and convenient detection of these toxic materials.